(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This article aims to describe the implementation of the Community Service Program (PkM) in improving the competencies of the school community at SMA Negeri 2 Lolofitu Moi. The study employed a qualitative approach using Action Research consisting of four stages: planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The implementation of the program included debate training, choir training, Canva application training, the Green School program through water spinach cultivation, and social service activities. The findings indicate that the implementation of the Community Service Program improved the competencies of the school community, including communication skills, critical thinking, digital competence, collaboration, environmental awareness, discipline, responsibility, and teamwork. The collaboration between the university and the school also strengthened the implementation of sustainable educational empowerment activities. It can be concluded that the Community Service Program is an effective strategy for improving the competencies of principals, teachers, educational staff, and students through integrated and sustainable activities